Aesthetics Problematics in Chinese and Neο-Marxism: Between Art and Politics - Vitalii Turenko (International Society of Philosophy and Cosmology, 2022)
The article reveals the features of the formation and functioning of aesthetic research in such two areas of Marxism as Chinese and Frankfurt Schools. Proved that in China, culture and the cultural revolution are inextricably linked with the Marxist projects of critiquing capitalist modernity and building alternative modernity. Aesthetics and culture also were at the center of attention in Chinese Marxist circles. In this respect, the diverse practices and designs of Chinese Marxism are similar to those of Western Marxism or an equally distinct variety of Euro-American Marxist intellectual enterprises. Aesthetic Marxism in China had a dual mission - to criticize the internal contradictions of revolutionary hegemony and to offer a constructive vision of culture in a post-revolutionary society. This is the value of Chinese aesthetic Marxism, the implications of which go beyond China proper in the world of global cultural criticism. Moreover, being non-Western, Chinese aesthetic Marxism deliberately questioned the inherent Eurocentrism of Marxism. If this Eurocentrism is to be challenged and problematized, the questions posed by Chinese aesthetic Marxists cannot be ignored. It was revealed that the representatives of Western Marxism, represented by such thinkers of the Frankfurt School as Theodor Adorno and Herbert Marcuse, saw the disclosure of the meaning of art and aesthetic research in general due to the fact that rational thinking initially has a drawback - it is repressive, associated with domination and the will to power. In contrast to this, true art, according to European neo-Marxist philosophers, expresses the truth of human existence in harmonious unity with nature, when a person does not oppose himself to it with his consciousness, but becomes like it and its creative forces.